The Xylocaine Test As A Prognostic Aid For Surgery In Sluder’S Neuralgia - Bader, Hani Musa; Mohammed, Mazin M.; Ahmed, Mohammed D. (Journal of the Faculty of Medicine Baghdad, 2007)
Summary: Background: Patients with facial pain without any overt disease especially of the nose and paranasal sinuses are often diagnosed as having Sluder’s neuralgia. Large middle turbinates or septal deflections compressing the ethmoidal nerves have been regarded as one of the causes of this pain in those who have their sinus computed tomography (CT) clear. Fac Med Baghdad Objectives: To evaluate the xylocaine test as a prognostic aid for surgical treatment for Sluder’s 2007; Vol. 49, No.3 neuralgia. Received Dec 2006 Methods: Sixty-one cases were seen; all of them had the xylocaine test positive. They were treated Accepted April 2007 surgically by endoscopic middle turbinectomy or septal surgery. Results: All had relieffrom the symptoms 4 months post operatively, except in five cases relief M’as achieved after revision surgeries for intranasal synechiae. Conclusion: The xylocaine (10 per cent) test seemed to be a good prognostic aid for the surgical procedures for those with Sluder’s neuralgia when medical treatment did not seem to relieve the symptom.